Comparison of heat monitoring-based myocardial protection strategy with classic myocardial protection method in isolated coronary artery bypass surgery patients - AK, KORAY (ELSEVIER SCIENCE INC, 2020)
Objective: In this study, we aimed to compare patients who have a myocardial protection strategy based on myocardial temperature monitorization with those who had myocardial protection with conventional intermittent cardioplegia. Methods: Twenty-six patients undergoing coronary artery bypass graft surgery were included into the study. Patients were prospectively grouped into two; myocardial protection based on temperature monitoring (group 1, n = 11) and those who had cardioplegia every 20 min (group 2, n = 15) during aortic cross-clamping. In all patients, cold blood cardioplegia was used. Coronary sinus blood sampling was performed immediately before aortic cross-clamping, after 2, 20, and 40 min of aortic clamping and tumor necrosis factor-alpha, malondialdehyde, creatinine kinase-myocardial band isoenzyme (MB), troponin I, lactate, and pH were studied. In addition, myocardial biopsy was taken before and immediately after cross-clamping to evaluate cardiomyocyte apoptosis with caspase-3 tunnel immunostaining. Results: There were no differences in clinical parameters like early mortality, extubation time, inotropic requirements, postoperative drainage, intensive care unit, and hospitalization time between two groups. In addition, blood and blood products were similar in two groups. In group 2, after cross-clamping, troponin I and creatinine kinase-MB values were significantly higher than the other group. In myocardial biopsies, the caspase immunostaining score, before removal of aortic cross-clamp was significantly higher in group 2 than the samples taken before aortic clamping. Conclusion: Our results show that there is no difference between temperature-based myocardial protection strategy with conventional intermittent cardioplegia delivery. We think that the number of patients in our study is less and that the patient population is not a homogeneous structure is the most important limiting factor of our study. Increasing the number of patients, with particularly those who have myocardial dysfunction would help augment the possible different effects of two cardioplegic techniques on myocardial protection. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Myocardial protection; Temperature monitoring myocardial; Ischemic reperfusion injury; Caspase-3; TNF-alpha; Malondialdehyde; ISCHEMIA-REPERFUSION INJURY; ENERGY-DEPLETED HEARTS; BLOOD CARDIOPLEGIA; RETROGRADE CARDIOPLEGIA; APOPTOSIS; ANTEGRADE; MECHANISMS; INDUCTION; DISEASE